Rekonstruksi Pembagian Warisan Islam Melalui Pendekatan Keadilan Gender - Amalia, Nur; Halim, Patimah (Universitas Islam Negeri Alauddin Makassar, 2024)
Equity in the division of inheritance between men and women continues to be a relevant and ongoing topic of discussion. The traditional view held by some classical circles is that the division of inheritance between men and women, as written in Surah An-Nisa' verse 11, is final and cannot be changed. Any change to this provision is considered a deviation from the sharia. On the other hand, contemporary scholars see the division as a rule that must be contextualized in accordance with the times and the existing social dynamics. Progressive thinking in this case is spearheaded by gender activists who consider that fiqh mawaris still has a gender bias. This study aims to analyze the application of the distribution of inheritance property that is fairer and in accordance with the conditions of Indonesian society through a gender theory approach. The methodology used is descriptive analytical, focusing on the issue of the distribution of inheritance that applies 1:2 for men and women. Data analysis was conducted by examining the arguments of inheritance through a socio-historical approach. The results show that the division of inheritance in Islam which refers to the ratio of 1:2 is not final. In the context of a changing society, the division can be adjusted to 1:1 or even 2:1. This research emphasizes the importance of contextual understanding of sharia texts so that the goal of Islamic law can be achieved, namely balanced justice for all parties. With this approach, it is hoped that the inheritance system can adapt to the more progressive values of gender justice in modern society.